MS, pregnancy and COVID-19 - Yam, Charmaine (Mult Scler, 2020)
Concerns regarding infection with the novel coronavirus SARS-CoV-2 leading to COVID-19 are particularly marked for pregnant women with autoimmune diseases such as multiple sclerosis (MS). There is currently a relative paucity of information to guide advice given to and the clinical management of these individuals. Much of the limited available data around COVID-19 and pregnancy derives from the obstetric literature, and as such, neurologists may not be familiar with the general principles underlying current advice. In this article, we discuss the impact of potential infection on the pregnant woman, the impact on her baby, the impact of the current pandemic on antenatal care, and the interaction between COVID-19, MS and pregnancy. This review provides a framework for neurologists to use to guide the individualised advice given to both pregnant women with MS, and those women with MS who are considering pregnancy. This includes evidence derived from previous novel coronavirus infections, and emerging evidence from the current pandemic.